2021
DOI: 10.1111/bjc.12324
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of schema therapy for patients with anxiety disorders, OCD, or PTSD: A systematic review and research agenda

Abstract: Objectives. We reviewed the evidence regarding the effectiveness of schema therapy for anxiety disorders, obsessive-compulsive disorder (OCD), and posttraumatic stress disorder (PTSD).Methods. This systematic review followed the recommendation of the PRISMA guidelines. A database search (PsycINFO, MEDLINE, EMBASE, WEB OF SCIENCE, and Academic Search Ultimate) was conducted to identify eligible studies up until 2 April 2021. The search included the keywords ('schema therap*' or 'schema group therap*' or 'schema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 67 publications
4
31
0
1
Order By: Relevance
“…Negative schemas are the outcomes of unmet core emotional needs in childhood and/or adolescence (i.e., acceptance, autonomy, reasonable limits, realistic expectations, and connection) and are elaborated upon throughout one's lifetime (Young et al, 2003). Empirical studies have found that negative schemas are the transdiagnostic mechanisms of personality and affective disorders (Wang et al, 2010;Bamelis et al, 2014;Peeters et al, 2021). However, individuals with maladaptive schemas in some areas can also have adaptive or positive schemas in other areas.…”
Section: Introductionmentioning
confidence: 99%
“…Negative schemas are the outcomes of unmet core emotional needs in childhood and/or adolescence (i.e., acceptance, autonomy, reasonable limits, realistic expectations, and connection) and are elaborated upon throughout one's lifetime (Young et al, 2003). Empirical studies have found that negative schemas are the transdiagnostic mechanisms of personality and affective disorders (Wang et al, 2010;Bamelis et al, 2014;Peeters et al, 2021). However, individuals with maladaptive schemas in some areas can also have adaptive or positive schemas in other areas.…”
Section: Introductionmentioning
confidence: 99%
“…Early maladaptive schemas are one of the core risk factors in the development of psychopathology (Young et al, 2003). Schema therapy is becoming more and more popular (Bach & Bernstein, 2019) and seems to be effective in treating different mental disorders (Oud et al, 2018;Carter et al, 2013;Jacob & Arntz, 2013;Peeters et al, 2021). Thus, it is important and of interest to know how the specific schemas are related to different types of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ST has been shown to be effective for personality disorders [e.g., ( 2 , 3 )]. The effectiveness of ST has further been examined for a range of other psychiatric diagnoses, including, but not limited to, depression [e.g., ( 4 )], anxiety disorders ( 5 ), and eating disorders [e.g., ( 6 )]. Young ( 7 ) defines EMSs as “extremely stable and enduring themes that develop during childhood, are elaborated throughout an individual's lifetime and are dysfunctional to a significant degree” (p. 9).…”
Section: Introductionmentioning
confidence: 99%